Role of Platelet-Derived Growth Factor-mediated signaling in carcinogenesis and metastasis: Role of PDGF/PDGFR pathway in cancer - Farooqi, Ammad Ahmad; Attar, Rukset (Cellular and Molecular Biology, 2023)
Platelet-Derived Growth Factor (PDGF) mediated signaling has emerged as one of the most extensively studied cascades in cancer development and progression. Overwhelmingly increasing data obtained from preclinical and clinical studies has helped us to develop a near-complete resolution of PDGF/PDGFR signaling landscape. Phenotype- and genotype-driven studies have provided proof-of-concept that therapeutic targeting of PDGF/PDGFR signaling axis is necessary to improve clinical outcome. Kinase inhibitor drug discovery programmes have broadened their focus to include a wide variety of kinase targets. Based on the insights gleaned from previously published high-impact research, it is clear that different transduction cascades crosstalk with PDGF/PDGFR signaling during primary tumor invasion, dissemination and ultimate metastasis of cancer cells. In this commentary, we will focus on involvement of PDGF/PDGFR signaling in different cancers and how pharmacological targeting of this signaling cascade inhibits cancer progression.